The Role of Patient-Site Facilitators in Teleaudiology: A Scoping Review. - Coco, Laura; Davidson, Alyssa; Marrone, Nicole (American Journal of Audiology)
Purpose: Teleaudiology helps improve access to hearing health care by overcoming the geographic gap between providers and patients. In many teleaudiology encounters, a facilitator is needed at the patient site to help with handson aspects of procedures. The aim of this study was to review the scope and nature of research around patient-site facilitators in teleaudiology. We focused on identifying the facilitators' background, training, and responsibilities. Method: To conduct this scoping review, we searched PubMed, CINAHL, and Embase. To be included, studies needed to address teleaudiology; be experimental/quasiexperimental, correlational/predictive, or descriptive; be published in English; and include the use of a facilitator at the patient location. Results: A total of 82 studies met the inclusion criteria. The available literature described a number of different individuals in the role of the patient-site facilitator, including audiologists, students, and local aides. Fifty-seven unique tasks were identified, including orienting the client to the space, assisting with technology, and assisting with audiology procedures. The largest number of studies (n = 42) did not describe the facilitators' training. When reported, the facilitators' training was heterogenous in terms of who delivered the training, the length of the training, and the training content. Conclusions: Across studies, the range of duties performed by patient-site facilitators indicates they may have an important role in teleaudiology. However, details are still needed surrounding their background, responsibilities, and training. Future research is warranted exploring the role of the patient-site facilitator, including their impact on teleaudiology service delivery.